MANAGEMENT MODEL LIMITED CASH TRANSACTIONSFOR THE ERADICATION OF CORRUPTION AND MONEY LAUNDERING IN INDONESIA - Qamarius, Ibrahim (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
This study aims to: 1) know the management of restrictions on cash transactions; 2) to know the response of the management of related state institutions to the limitation of cash transactions; 3) to know the involvement of human resources in the management of restrictions on cash transactions; 4) find out the amount of restrictions on cash transactions expected by the management of relevant state institutions; 5) to know the coordination and supervision among related state institutions in realizing the Law on Limitation of Cash Transaction in Indonesia. This study uses case study method in several state institutions, namely 1) Financial Transaction Reporting and Analysis Center: 2) Bank Indonesia; 3) National Legal Development Board, Ministry of Justice and Human Rights; And 4) of the People’s Legislative Assembly of the Republic of Indonesia. Data collection is done through observation, interview, documentation and focus group discussioin. Data analysis is done descriptively and qualitatively. The research resulted in: 1) the management of restrictions on cash transactions made with relevant state institutions already exist; 2) the responses of state institutions’ management to the very positive cash transaction restriction, in their view and their response that the restrictions on cash transactions will prevent corruption and various forms of money laundering in Indonesia; 3) all relevant state institutions have involved human resources in conducting studies and even been directly involved in meetings on restrictions on cash transactions; 4) for the initial phase all the relevant state institutions agree the amount of cash transaction restrictions Rp. 100,000,000, - (one hundred million rupiah); 5) coordination among related state institutions in realizing the Law on Restrictions on Cash Transactions in Indonesia has been well coordinated. Keywords: Management, Restrictions on Cash Transaction, CorruptionEradication, Money Laundering